Digitalisasi Penjadwalan Kegiatan Desa Berbasis Internet Of Things - Anita Sindar Sinaga; Nuraisana; R. Mahdalena Simanjorang; Bella Saputri; Nadia Aulia (Jurnal Visi Pengabdian Kepada Masyarakat, 2026)
Digitalization of village community activity scheduling based on the Internet of Things (IoT) can increase efficiency, transparency, and community participation in village activities. The development of Internet of Things (IoT) technology for village activity scheduling encourages real-time and automatic activity information to be presented without manual announcements, the system is able to provide time reminders and digital notifications, reduce the administrative burden on village officials and increase community participation through fast and accurate access to information. Evaluation of system development activities in Naga Kisar illustrates the development of the level of success of activities from the initial stage to the final stage of implementation. The benefits to village services amounted to 92%, which indicates that the system has a significant positive impact on improving the quality of village services.